Cryotherapy on exfoliative cytological changes for oral mucositis in cancer patients undergoing chemotherapy: A randomized control trial - Erika, Kadek A.; Mulhaeriah, Mulhaeriah; Miskad, Upik A.; Zuraida, Eli; Sangkala, Moh S.; Magfirah, Ika; Achmad, Harun (Narra Sains Indonesia, 2025)
Oral mucositis is a common complication of chemotherapy that significantly impacts quality of life and may reduce treatment efficacy. While oral cryotherapy has been widely studied as a preventive intervention due to its cost-effectiveness, safety, and ease of use, most research focused on clinical outcomes without incorporating objective cytological assessments of mucosal changes. The aim of this study was to evaluate the effectiveness of oral cryotherapy in managing chemotherapy-induced mucositis using exfoliative cytology to monitor oral mucosal changes. A single-blinded, randomized controlled trial was conducted involving 50 cancer patients undergoing chemotherapy, who were randomly assigned to either the intervention or control group. The control group (n=25) received standard oral hygiene care, while the intervention group (n=25) received oral cryotherapy in addition to routine oral hygiene. A 20-minute oral cryotherapy was administered twice daily after breakfast (09:00 A.M.) and lunch (01:00 P.M.) for 14 days. This study found a significant reduction in mucositis scores was observed in both groups (p<0.05). However, post-hoc analysis indicated that mucositis severity declined earlier in the cryotherapy group, whereas improvement in the control group was noted only after 14 days. Serial oral mucosal smears analyzed via exfoliative cytology revealed a reduction in inflammatory cells and the absence of coccus microorganisms by days 7 and 14 in the intervention group. In conclusion, this study demonstrated that oral cryotherapy effectively reduces the severity and duration of mucositis and accelerates recovery in cancer patients undergoing chemotherapy. Oral cryotherapy can be applied as a viable alternative to mitigate the severity of oral mucositis in this patient population.